The maintenance of flat roof in residential building / Aspalela Othman - Othman, Aspalela (Faculty of Architecture, Planning and Surveying, 2013)
Malaysian architecture always synonym with the significant in traditional pitched roof design whereby most of the roof are built in such a way to suit with the climatic reasons and also for the aesthetical value. However, as time goes on, new era emerge with a modem lifestyle that has forced the adaptation of new building technology' and design in our housing culture and development. This is why flat roof design has been adapted, applied and becomes more established in housing development in Malaysia to suit the modem lifestyle. Flat roof design in residential building is not that new in Malaysia as it hasbeen adapted in Malaysia ever since the early modem movement hit the world architectural style and followed by the global spread through the international style. More and more housing development dares to apply the design concept in residential building despite the bad image it carries all along in the building industry. The climatic reasons have been always described as the causes of such problems in flat roof However, despite the problem of the flat roof, its flexibility and creativity' of the design, function and aesthetic value gain highly demand in the residential building development and attract purchaser to invest. The need to study on flat roof is to determine the problems of flat roof design in residential buildings that still occur despite the vast development of building technology and materials and to analyze the common type of maintenance for the flat roof. Most problems which influenced by various aspects such as the design, details and specification, construction and materials are discussed in line with the knowledge of the people and a need of a suitable maintenance to be carried out in order to sustain the performance and long life of the flat roof regardless the type of the residential building.